XR, AI, IoT, and 5G Applications in Fight Against the COVID-19 Pandemic - Mete, Anı Hande; Türkön, Buse Fidan; Yılmaz, Faruk; İnce, Özgür (İzmir Katip Çelebi Üniversitesi, 2023)
To struggle the devastating impact of the Coronavirus disease pandemic, governments have had to implement containment and closure policies. While these practices caused the disruption of activities in many sectors, on the contrary, they led to an increase in demand for healthcare, making it necessary to operate above the capacity to make control of contagious. In this context, there has been an increase in the use of innovative technologies such as extended reality, artificial intelligence, internet of things, and 5G in order to effectively fight against the pandemic. In this review, it is aimed to reveal the fields of usage and model implementation of related innovative technologies during the pandemic process. These technologies have provided various benefits for health facilities, health workers, patients, and health systems, in many areas such as the delivery of health care for COVID-19, application of diagnosis and treatment methods, medical education, public health, and health promotion. These benefits can be summarized as improving customer service and quality, saving resources and providing competitive advantages for health facilities; protecting and promoting health, ensuring patient safety and cost savings for patients; providing a safe working environment for health care workers; providing effective capacity utilization and balance between supply and demand for healthcare, health care worker training, improving public health, propounding data reliability and traceability for healthcare systems. In crisis situations such as like a pandemics in healthcare processes, governments must inevitably use innovative technologies. In this context, it is important to consider these technologies while developing policies for both workforce training and existing infrastructure in healthcare.

Koronavirüs hastalığı pandemisinin yıkıcı etkisiyle mücadelede hükümetler, sınırlama ve kapanma politikaları uygulamak durumunda kalmıştır. Bu uygulamalar pek çok sektörde faaliyetlerin aksamasına sebep olurken, sağlık hizmetleri sektöründe aksine talep artışına yol açarak bulaşıcılığın kontrolünü sağlayacak şekilde kapasite üzerinde faaliyet gösterilmesini gerekli kılmıştır. Bu kapsamda pandemi ile etkin bir şekilde mücadele edebilmek için genişletilmiş gerçeklik, yapay zekâ, nesnelerin interneti ve 5G gibi yenilikçi teknolojilerin kullanımında artış görülmüştür. Bu derlemede pandemi sürecinde ilgili yenilikçi teknolojilerin kullanım alanlarının ve örnek uygulamalarının ortaya konulması amaçlanmaktadır. Bu teknolojiler, COVID-19’a yönelik sağlık hizmetlerinin sunumu, teşhis ve tedavi yöntemlerinin uygulanması, tıp eğitimi, halk sağlığı ve sağlığın geliştirilmesi gibi pek çok alanda sağlık işletmeleri, sağlık çalışanları, hastalar ve bir bütün olarak sağlık sistemleri için çeşitli faydalar sağlamıştır. Bu faydalar sağlık işletmeleri için müşteri hizmetleri ve kalitenin geliştirilmesi, kaynak tasarrufu ve rekabet üstünlüğünün sağlanması; hastalar açısından sağlığın korunması ve geliştirilmesi, hasta güvenliğinin ve maliyet tasarrufunun sağlanması; sağlık çalışanları için daha güvenli bir çalışma ortamının sağlanması; sağlık sistemlerine ise etkin kapasite kullanımı, sağlık hizmetleri arz ve talep dengesinin sağlanması, sağlık insan gücü eğitimi, halk sağlığının geliştirilmesi, veri güvenilirliği ve izlenebilirliğinin sağlanması olarak özetlenebilir. Sağlık hizmeti süreçlerinde pandemi gibi kriz durumlarında hükümetlerin yenilikçi teknolojileri kaçınılmaz olarak kullanması gerekmektedir. Bu doğrultuda sağlık hizmetlerinde ortaya çıkan ihtiyaçları karşılayabilmek için bu teknolojilerin hem insan gücü yetiştirme hem de mevcut altyapıya yönelik politikaların geliştirilmesinde kullanımı önem arz etmektedir.
COVID-19 Pandemisi ile Mücadelede XR, AI, IoT ve 5G Uygulamaları
Keywords: COVID-19; Artificial Intelligence; Internet of Things; virtual reality; augmented reality.; COVID-19; Yapay Zekâ; Nesnelerin İnterneti; Sanal Gerçeklik; Artırılmış Gerçeklik; virtual reality; augmented reality.